2019
DOI: 10.1007/s00439-019-02069-7
|View full text |Cite
|
Sign up to set email alerts
|

A different view on fine-scale population structure in Western African populations

Abstract: Due to its long genetic evolutionary history, Africans exhibit more genetic variation than any other population in the world. Their genetic diversity further lends itself to subdivisions of Africans into groups of individuals with a genetic similarity of varying degrees of granularity. It remains challenging to detect fine-scale structure in a computationally efficient and meaningful way. In this paper, we present a proof-of-concept of a novel fine-scale population structure detection tool with Western African… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Indeed, as Haldane noted, only a small gain in fitness would be required for a variant to attain its equilibrium frequency ( 8 ). The strongest SCT protective effect has now been recorded in West African (Gambia), whereas the weakest effect was recorded in Cameroon, although it is unclear whether fine-scale genetic sub-structure in Cameroon may have confounded these analyses ( 11 , 12 ).…”
Section: Common Variants In Haemoglobin Genesmentioning
confidence: 99%
“…Indeed, as Haldane noted, only a small gain in fitness would be required for a variant to attain its equilibrium frequency ( 8 ). The strongest SCT protective effect has now been recorded in West African (Gambia), whereas the weakest effect was recorded in Cameroon, although it is unclear whether fine-scale genetic sub-structure in Cameroon may have confounded these analyses ( 11 , 12 ).…”
Section: Common Variants In Haemoglobin Genesmentioning
confidence: 99%
“…IBD-based methods are only useful for very recent population developments. Another study [12] used a very different method of iteratively pruned Principal Component Analysis to investigate the much older population structure of West Africa.…”
Section: Population Structure Inference and Admixture Mappingmentioning
confidence: 99%
“…Identification of genes underlying ALS has provided critical insights into the cellular mechanisms leading to neurodegeneration, such as protein homeostasis, cytoskeleton alterations, RNA metabolism, endoplasmic reticulum stress, nucleocytoplasmic transport, and autophagy defects (Saez-Atienzar et al 2021). The genome-wide association study of Western African populations reported that 46 genes out of 165 genes were linked to sporadic ALS in the population (Chaichoompu et al 2020). A recent study that systematically applied a polygenic risk score analysis to a genomic dataset involving 78,500 individuals to distinguish the cellular processes driving ALS, has reported six differentially expressed genes (ATG16L2, ACSL5, MAP1LC3A, MAPKAPK3, PLXNB2, and SCFD1) within the significant pathways that are relevant to ALS (Saez-Atienzar et al 2021).…”
Section: Introductionmentioning
confidence: 99%